Pengaruh Role Conflict, Role Ambiguity dan Role Overload terhadap Cyberloafing pada Karyawan CV. Mekanika Engineering Bengkulu - Islamuddin Islamuddin; Mutiara Winda Giatri; Meilaty Finthariasari; Indramawan Kusuma Trisna (Universitas Batanghari, 2023)
The aims of study is to analyze the effect of Role Conflict, Role Ambiguity and Role Overload on Cyberloafing in Employees of CV. Bengkulu Engineering Mechanics. This researchnis a quantitativendescriptive research with the object of research being employees of CV. Bengkulu Engineering Mechanics. The sample consisted of 33 people, drawn using Stratified Random Sampling. Data was collected using a questionnaire, and processed using SPSS version 26. The results showed that the variable Role Conflict had a positive and significant effect on Cyberloafing, Role Ambiguity had a positive and significant effect on Cyberloafing, and And Role Overload had a negative and significant effect on Cyberloafing.